Strategi Komunikasi Humas Universitas Tarumanagara selama Pandemi Covid-19 - Shinta Darmawaty; Septia Winduwati (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Public Relations in University has a core role such as forming and maintaining a positive image in the eyes of the public, especially during a pandemic like this all communication must be done online, this requires that Public Relations in university must be able to take advantage of digital technology. The purpose of this research is to find out how the PR communication strategy of a private university, in this case, Tarumanagara University during the Covid-19 pandemic. This study uses a theoretical foundation in the form of communication, communication strategies, internal and external stakeholders, and public relations of educational institutions, with a qualitative research approach, a case study method which is one of the research strategies to develop an in-depth analysis with the subject matter of the communication strategies applied by University Public Relations. Tarumanagara during the Covid-19 pandemic. During the pandemic, Public Relations of Tarumanagara University delivered messages using an informal message delivery method, and the messages arranged were also adjusted depending on who the audience was, to find out who the audience was Public Relations of Tarumanagara University divided into two types of audiences, such as internal audiences consisting of Lecturers , employees and students, as well as external audiences consisting of the Government, the media, the surrounding community (community), alumni, and the general public. Social and digital media have become the most reliable means of communication during the Covid-19 pandemic.Humas Perguruan Tinggi Swasta (PTS) memiliki peranan inti seperti membentuk dan memperthankan citra positif di mata publiknya, terlebih lagi pada saat pandemi seperti ini semua komunikasi harus dilakukan secara daring, hal tersebut menuntut Humas PTS harus mampu dalam memanfaatkan teknologi digital. Tujuan dari penelitian ini adalah untuk untuk mengetahui bagaimana strategi komunikasi Humas Perguruan Tinggi Swasta dalam hal ini, Universitas Tarumanagara selama pandemi Covid-19. Penelitian ini menggunakan konsep teori komunikasi, strategi komunikasi, stakeholders internal dan eksternal, dan humas lembaga pendidikan, dengan metode penelitian kualitatif studi kasus dimana merupakan salah satu strategi penelitian untuk mengembangkan analisis mendalam dengan pokok masalah bagiamana startegi komunikasi yang diterapkan Humas Universitas Tarumanagara selama pandemi Covid-19. Hasil dari penelitian ini adalah, strategi komunikasi yang dilakukan Humas Untar selama pandemi Covid-19 adalah melakukan komunikasi secara daring baik kepada pihak internal dan eksternal, yang bertujuan untuk melindungi segenap anggota internal Universitas Tarumanagara dari resiko penularan virus Covid-19.